Fabrication of polymer microfiber by direct drawing - Irawati, Ninik; Suthaskumar, M.; John, V.; Ali, N.M.; Ahmad, Harith; Harun, Sulaiman Wadi (2015)
We report the fabrication of polymer microfiber with high surface smoothness and length uniformity using molten polymethyl methacrylate (PMMA) by direct drawing technique. PMMA microfibers with diameters ranging from 6 to 12 m and lengths up to few centimeters have been drawn by this method. The microfibers' losses are obtained at 0.37, 0.27, and 0.19 dB/mm for the microfibers with diameters of 6, 8, and 12 m, respectively. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:820-823, 2015